PENGARUH PENGEMBANGAN KARIR DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) AREA PEKANBARU RAYON KOTA TIMUR - Nia Uli Silitonga; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed to determine the effect of career development and discipline of work to employes performance at PT. PLN (Persero) Area Pekanbaru Rayon Kota Timur. With cencus sampling method as many as 41 people. The research data in the form of primary data and secondary data, with the questionnaire as a research instrument. Analysis of the data used by using SPSS.Result of analysis using multiple linier regression, t-test, and the test of determination (R2), career development of 0,797or 79,7% and work discipline of 0,561or 56,1% and the F-test. So that the figures obtained R2 (R Square) of 0,834, or 83,4% . this shows that the percentage contribution of independent variables (career development and discipline of work) on the dependent variable (performance of employes) amounted to 83,4% and strong relationships with a large award is 0,834. While the percentage of the remaining 16,6% (100%-83,4%) influenced by other variables not included in this study variablesKeywords : Career Development, Discipline Work, Employe Performance